AKSI PEPELINGAN (PENYULUHAN PEDULI LINGKUNGAN) - Aprilia Mukaromatun Barokah; Santia Ningrum; Bayu Adi Laksono (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Mangkubumi especially Sambongpari is still not aware of the environment. In addition, the source of water for rice fields is still using flowing rivers. This can make the river contaminated from household waste and garbage which is feared to affect the quality of crops and have an impact on human health. MCK is not in accordance with applicable regulations and well spacing is also not appropriate will cause soil contamination and soil pollution occurs. this is exacerbated by a consumptive society and a lack of community action in caring for the environment. in this case the researcher observes the activities carried out by the community regarding the area that will be used as the object of counseling. identification of problems and potential environmental impacts of observed activities. identify patterns of change or problems that arise. this asks questions to community leaders and related parties concerned with environmental care counseling related to the behavior and habits of the Mangkubumi community in order to find out how far the community has knowledge about environmental issues and how far they care about the environment. this will provide solutions and solutions to existing problems from environmental awareness counseling actions. This program was carried out on October 28, 2022 with the theme